Low-temperature curing type phosphate coating as well as preparation method and use method thereof

By using aluminum powder, phosphoric acid and other components in the inorganic phosphate coating, combined with low-temperature heat treatment and high-temperature heat treatment, the low-temperature curing and high-performance of the low-temperature curing phosphate coating is achieved, and the problems of high brittleness and insufficient low-temperature curing performance are solved.

CN119505582APending Publication Date: 2025-02-25CHENGDU BULEIDE TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411639950.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing inorganic phosphate coatings have limited their wide application in certain special fields due to their high brittleness and the need for high temperature curing. The low-temperature curing coatings have insufficient density and binding strength, resulting in poor comprehensive mechanical properties.

Method used

By preparing a low-temperature curing phosphate coating, the low-temperature curing and high-performance coating is achieved by combining aluminum powder, phosphoric acid, aluminum hydroxide, chromium anhydride, zirconium sol, polyvinyl alcohol coated with magnesium oxide, rare earth oxide, organic alcohol amine, fused quartz, nanosilica and fibers.

Benefits of technology

Low-temperature curing of the coating is achieved (to 150°C), and the cured coating has comprehensive mechanical properties comparable to that of traditional high-temperature curing phosphate coatings, solving the problem of degradation of coating performance after low-temperature curing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a low-temperature curing type phosphate coating as well as a preparation method and a use method thereof, and belongs to the technical field of phosphate coatings. The polyvinyl alcohol is used for coating magnesium oxide, so that the dispersity of magnesium oxide in the coating can be improved, and the wear resistance and scratch resistance of the coating are enhanced; the magnesium oxide curing agent reacts with phosphate, so that the crosslinking curing temperature of the coating is reduced; by adding the organic alcohol amine, the low-temperature curing of the coating can be promoted, and the flexibility of the coating can be improved by the flexible chain segment of the organic alcohol amine, so that the coating material shows excellent comprehensive mechanical properties; by adding the rare earth oxide, the conductivity of the coating can be improved, the conductivity of the coating is optimized, and then the corrosion resistance of the coating is improved; gaps and cracks in the coating can be filled with the added fused quartz, nano silicon dioxide and fibers, the compactness of the coating is improved, and then the comprehensive mechanical property of the coating is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of phosphate coatings, and in particular to a low-temperature curing phosphate coating and a preparation method and a use method thereof. Background Art

[0002] Inorganic phosphate metal aluminum powder coating is a coating formed by curing divalent and trivalent metal phosphates, chromates and aluminum powder. It has good high temperature resistance, oxidation resistance, salt spray resistance and radiation resistance, and is widely used in the fields of aerospace, steam turbines, and industrial compressor parts corrosion protection. However, due to the amorphous structure of inorganic phosphates themselves, it has high brittleness. In addition, the curing temperature of inorganic phosphate coatings exceeds 310°C, and the dehydration reaction between molecules will be thorough and the coating will be completely cured. Otherwise, the coating will be damp, resulting in reduced bonding strength, conductivity and corrosion resistance of the coating. Therefore, the high brittleness of inorganic phosphate coatings and the need for high temperature curing seriously limit their wide application in certain special fields.

[0003] At present, various types of low-temperature or even room-temperature curing inorganic phosphate composite coating materials have been prepared in the prior art. For example, magnesium oxide, copper oxide, chromium trioxide, silicate and phosphate are used as curing agents to obtain low-temperature phosphate coatings. However, although the above curing agents can reduce the curing temperature, the density of the cured coating becomes poor and the bonding force with the substrate becomes weak, resulting in poor comprehensive mechanical properties of the coating.

[0004] Therefore, there is an urgent need to develop a low-temperature curing phosphate coating with a low curing temperature and high comprehensive mechanical properties of the cured coating. Summary of the invention

[0005] The object of the present invention is to provide a low-temperature curing phosphate coating and a preparation method and a use method thereof. The low-temperature curing phosphate coating provided by the present invention has a low curing temperature, and the cured coating has high comprehensive mechanical properties.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The invention provides a low-temperature curing phosphate coating, which is prepared from raw materials comprising the following components by mass content: 40-70% aluminum powder, 6-15% phosphoric acid, 2-5% aluminum hydroxide, 1-3% chromic anhydride, 5-10% zirconium sol, 1-2% polyvinyl alcohol-coated magnesium oxide, 0.5-2% rare earth oxide, 1.5-3% organic alcohol amine, 0.5-3% fused quartz, 0.5-5% nano silicon dioxide, 0.5-5% fiber and the balance of water.

[0007] Preferably, the method for preparing the polyvinyl alcohol-coated magnesium oxide comprises: mixing magnesium oxide, polyvinyl alcohol and water to obtain the polyvinyl alcohol-coated magnesium oxide.

[0008] Preferably, the rare earth oxide comprises cerium oxide and / or lanthanum oxide.

[0009] Preferably, the organic alcoholamine includes ethanolamine, diethanolamine or isopropanolamine.

[0010] Preferably, the particle size of the fused quartz is 5-10 μm.

[0011] Preferably, the particle size of the nano-silicon dioxide is 5-20 nm.

[0012] Preferably, the diameter of the fiber is 5-20 μm; the length of the fiber is 50-100 μm.

[0013] Preferably, the fibers comprise glass fibers and / or silica fibers.

[0014] The present invention also provides a method for preparing the low-temperature curing phosphate coating according to the above technical solution, comprising the following steps: (1) mixing phosphoric acid, aluminum hydroxide, chromic anhydride and water to obtain a mixed slurry; (2) mixing polyvinyl alcohol-coated magnesium oxide, rare earth oxide and organic alcohol amine with the slurry obtained in step (1) to obtain a binder; (3) Aluminum powder, zirconium sol, fused quartz, nano-silicon dioxide and fiber are mixed with the binder obtained in step (2) to obtain a low-temperature curing phosphate coating.

[0015] The present invention also provides a method for using the low-temperature curing phosphate coating described in the above technical solution or the low-temperature curing phosphate coating prepared by the preparation method described in the above technical solution, comprising: applying the low-temperature curing phosphate coating to a substrate, and sequentially performing low-temperature heat treatment and high-temperature heat treatment to obtain a coating; The temperature of the low-temperature heat treatment is 60-80°C, and the insulation time of the low-temperature heat treatment is 30-120 minutes; the temperature of the high-temperature heat treatment is 150-200°C, and the insulation time of the high-temperature heat treatment is 30-120 minutes.

[0016] The invention provides a low-temperature curing phosphate coating, which is prepared from raw materials comprising the following components by mass content: 40-70% aluminum powder, 6-15% phosphoric acid, 2-5% aluminum hydroxide, 1-3% chromic anhydride, 5-10% zirconium sol, 1-2% polyvinyl alcohol-coated magnesium oxide, 0.5-2% rare earth oxide, 1.5-3% organic alcohol amine, 0.5-3% fused quartz, 0.5-5% nano silicon dioxide, 0.5-5% fiber and the balance of water. The coating provided by the present invention adds aluminum powder, and uses the aluminum powder to react with phosphate to form an aluminum phosphate complex, and the complex can enhance the chemical stability and adhesion of the coating; the present invention adds chromic anhydride, and in the initial stage of temperature rise and curing when the coating is used, the low melting point characteristic of chromic anhydride helps to form a gel-like film-like substance, which helps to improve the density of the coating and reduce the microporous structure of the coating; the present invention can improve the bonding ability between the coating and the substrate by adding zirconium sol; the present invention uses polyvinyl alcohol to coat magnesium oxide, and the coating effect of polyvinyl alcohol can improve the dispersibility of magnesium oxide in the coating, effectively prevent the aggregation of magnesium oxide particles, ensure the uniform distribution of the coating, avoid the agglomeration of the coating, and enhance the wear resistance and scratch resistance of the coating; the present invention uses a magnesium oxide curing agent to react with phosphate, thereby reducing the cross-linking curing temperature of the coating; the present invention adds an organic As a curing agent, alcohol amine can not only promote the low-temperature curing of phosphate coatings, but also its flexible segments can improve the flexibility of the coating, so that the coating material exhibits excellent comprehensive mechanical properties; the present invention can improve the conductivity of the coating by adding rare earth oxides, optimize the conductive properties of the coating, and thus improve the anti-corrosion performance of the coating; the present invention uses fused quartz as aggregate to make the coating have higher mechanical strength, and at the same time is conducive to improving the adhesion of the coating; the present invention uses nano-silicon dioxide as a thickening and weathering component to improve the strength and weathering resistance of the coating; the present invention uses fiber as a filler, and when the coating is cured, the binder will spread along the fiber to improve the compactness of the coating; and the fused quartz, nano-silicon dioxide and fiber added by the present invention can fill the gaps and cracks in the coating, improve the compactness of the coating, and thus improve the comprehensive mechanical properties of the coating. The results of the embodiment show that the curing temperature of the coating provided by the present invention is as low as 150°C, and the coating has comprehensive mechanical properties comparable to those of traditional high-temperature cured phosphate coatings. DETAILED DESCRIPTION

[0017] The invention provides a low-temperature curing phosphate coating, which is prepared from raw materials comprising the following components by mass content: 40-70% aluminum powder, 6-15% phosphoric acid, 2-5% aluminum hydroxide, 1-3% chromic anhydride, 5-10% zirconium sol, 1-2% polyvinyl alcohol-coated magnesium oxide, 0.5-2% rare earth oxide, 1.5-3% organic alcohol amine, 0.5-3% fused quartz, 0.5-5% nano silicon dioxide, 0.5-5% fiber and the balance of water.

[0018] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known to those skilled in the art.

[0019] In the present invention, the raw materials for preparing the low-temperature curing phosphate coating include aluminum powder with a mass content of 40-70%, preferably 50-65%, and more preferably 55-60%. The present invention utilizes aluminum powder to react with phosphate to form an aluminum phosphate complex, which can enhance the chemical stability and adhesion of the coating. The present invention has no special restrictions on the size of the aluminum powder, and conventional commercially available aluminum powder can be used.

[0020] In the present invention, the raw material for preparing the low-temperature curing phosphate coating includes phosphoric acid with a mass content of 6 to 15%, preferably 8 to 12%, and more preferably 10 to 12%. The present invention has no special limitation on the concentration of the phosphoric acid, and conventional commercially available phosphoric acid can be used. In an embodiment of the present invention, the phosphoric acid is industrial phosphoric acid with a mass concentration of 85%.

[0021] In the present invention, the raw materials for preparing the low-temperature curing phosphate coating include aluminum hydroxide with a mass content of 2-5%, preferably 3-4%. In the present invention, phosphoric acid and aluminum hydroxide are added to the coating to form an aluminum phosphate compound as the main component of the coating.

[0022] In the present invention, the raw materials for preparing the low-temperature curing phosphate coating include chromic anhydride with a mass content of 1-3%, preferably 2-3%. In the present invention, by adding chromic anhydride, when the coating is used, in the initial stage of temperature rise and curing, the low melting point property of chromic anhydride helps to form a gel-like film-like substance, which helps to improve the density of the coating and reduce the microporous structure of the coating.

[0023] In the present invention, the raw materials for preparing the low-temperature curing phosphate coating include zirconium sol with a mass content of 5-10%, preferably 6-8%. The present invention can improve the bonding ability between the coating and the substrate by adding zirconium sol.

[0024] In the present invention, the raw materials for preparing the low-temperature curing phosphate coating include polyvinyl alcohol-coated magnesium oxide with a mass content of 1-2%, preferably 1.5-2%. The present invention uses polyvinyl alcohol-coated magnesium oxide as a curing agent. The coating effect of polyvinyl alcohol can improve the dispersion of magnesium oxide in the coating, effectively prevent the aggregation of magnesium oxide particles, ensure the uniform distribution of the coating, avoid the agglomeration of the coating, and enhance the wear resistance and scratch resistance of the coating.

[0025] In the present invention, the method for preparing the polyvinyl alcohol-coated magnesium oxide preferably comprises: mixing magnesium oxide, polyvinyl alcohol and water to obtain the polyvinyl alcohol-coated magnesium oxide.

[0026] The present invention has no special limitation on the particle size of the magnesium oxide, and any conventional commercially available magnesium oxide powder may be used.

[0027] The present invention has no special limitation on the molecular weight of the polyvinyl alcohol, and any conventional commercially available polyvinyl alcohol can be used. In an embodiment of the present invention, the polyvinyl alcohol is polyvinyl alcohol 1788 or polyvinyl alcohol 1989.

[0028] In the present invention, the mass ratio of magnesium oxide to polyvinyl alcohol is preferably (5-6): (1.5-2), more preferably 5: 1.5. The present invention controls the mass ratio of the two within the above range, which can improve the dispersibility of polyvinyl alcohol-coated magnesium oxide in the coating.

[0029] In the present invention, the ratio of the mass of magnesium oxide to the volume of water is preferably (5-6) g:300 mL, more preferably 5 g:300 mL. The present invention uses water as a mixing medium and controls its amount within the above range, which is more conducive to the full modification of magnesium oxide by polyvinyl alcohol.

[0030] In the present invention, the method of mixing magnesium oxide, polyvinyl alcohol and water is preferably ultrasound, and the ultrasound time is preferably 0.5 to 1 hour, more preferably 0.8 to 1 hour. The present invention can fully disperse magnesium oxide and polyvinyl alcohol through ultrasound, which is more conducive to more uniform packaging.

[0031] In the present invention, after mixing magnesium oxide, polyvinyl alcohol and water, the magnesium oxide, polyvinyl alcohol and water are preferably filtered, washed and dried in sequence to obtain polyvinyl alcohol-coated magnesium oxide. The present invention has no special restrictions on the operation methods of the filtering, washing and drying. Conventional filtering, washing and drying can be used to remove impurities and obtain dried polyvinyl alcohol-coated magnesium oxide. In an embodiment of the present invention, the washing agent is water, the drying temperature is 40° C., and the drying time is 24 hours.

[0032] In the present invention, the raw materials for preparing the low-temperature curing phosphate coating include rare earth oxides with a mass content of 0.5-2%, preferably 1-1.5%. In the present invention, the rare earth oxides preferably include cerium oxide and / or lanthanum oxide. The present invention can improve the conductivity of the coating by adding rare earth oxides, optimize the conductive properties of the coating, and thus improve the anti-corrosion performance of the coating.

[0033] In the present invention, the raw materials for preparing the low-temperature curing phosphate coating include an organic alcohol amine with a mass content of 1.5-3%, preferably 1.5-2%. In the present invention, the organic alcohol amine preferably includes ethanolamine, diethanolamine or isopropanolamine, more preferably ethanolamine or diethanolamine. The organic alcohol amine is added as a curing agent in the present invention, which can not only promote the low-temperature curing of the coating, but also the flexible segment can improve the flexibility of the coating, so that the coating material exhibits excellent comprehensive mechanical properties.

[0034] In the present invention, the raw material for preparing the low-temperature curing phosphate coating includes 0.5-3% by mass of fused quartz, preferably 1-2%. In the present invention, the particle size of the fused quartz is preferably 5-10 μm, more preferably 5-8 μm. By using fused quartz as an aggregate, the present invention makes the coating have a higher mechanical strength and is conducive to improving the adhesion of the coating.

[0035] In the present invention, the raw materials for preparing the low-temperature curing phosphate coating include nano-silicon dioxide with a mass content of 0.5-5%, preferably 2-5%. In the present invention, the particle size of the nano-silicon dioxide is preferably 5-20nm, more preferably 5-10nm. The present invention uses nano-silicon dioxide as a thickening and weathering component to improve the strength and weathering resistance of the coating.

[0036] In the present invention, the raw materials for preparing the low-temperature curing phosphate coating include fibers with a mass content of 0.5-5%, preferably 1-3%. In the present invention, the diameter of the fibers is preferably 5-20 μm, more preferably 10-20 μm; the length of the fibers is preferably 50-100 μm, more preferably 60-80 μm; the fibers preferably include glass fibers and / or silica fibers, more preferably glass fibers. The present invention uses fibers as fillers, and when the coating is cured, the binder will spread along the fibers to improve the density of the coating.

[0037] In the present invention, the preparation of the low temperature curing phosphate coating includes a balance of water. The present invention utilizes water as a dispersion medium for the coating.

[0038] The low-temperature curing phosphate coating provided by the present invention can cure the phosphate coating at low temperature by improving the coating components, and at the same time, the cured coating maintains good comprehensive mechanical properties.

[0039] The present invention also provides a method for preparing the low-temperature curing phosphate coating according to the above technical solution, comprising the following steps: (1) mixing phosphoric acid, aluminum hydroxide, chromic anhydride and water to obtain a mixed slurry; (2) mixing polyvinyl alcohol-coated magnesium oxide, rare earth oxide and organic alcohol amine with the slurry obtained in step (1) to obtain a binder; (3) Aluminum powder, zirconium sol, fused quartz, nano-silicon dioxide and fiber are mixed with the binder obtained in step (2) to obtain a low-temperature curing phosphate coating.

[0040] The invention mixes phosphoric acid, aluminum hydroxide, chromic anhydride and water to obtain mixed slurry.

[0041] In the present invention, the method of mixing the phosphoric acid, aluminum hydroxide, chromic anhydride and water is preferably to first stir and mix the phosphoric acid, chromic anhydride and water uniformly, then add aluminum hydroxide to the obtained mixed system, and continue stirring for 0.5 to 1 hour. In the present invention, the temperature of mixing the phosphoric acid, aluminum hydroxide, chromic anhydride and water is preferably 85 to 90°C.

[0042] After the mixed slurry is obtained, the present invention mixes the polyvinyl alcohol-coated magnesium oxide, rare earth oxide and organic alcohol amine with the mixed slurry to react and obtain a binder.

[0043] In the present invention, the temperature of the mixing reaction is preferably 85-90°C, more preferably 85°C; the time of the mixing reaction is preferably 0.5-1h, more preferably 1h. The present invention reacts under the above conditions, which is more conducive to the full reaction of the raw materials to obtain the binder.

[0044] In the present invention, the mixing reaction is preferably carried out under stirring. The present invention has no particular limitation on the stirring speed, which can be adjusted according to the dispersion conditions of each substance.

[0045] After obtaining the binder, the present invention mixes aluminum powder, zirconium sol, fused quartz, nano silicon dioxide and fiber with the binder to obtain a low-temperature curing phosphate coating.

[0046] In the present invention, the method of mixing the aluminum powder, zirconium sol, fused quartz, nano-silica and fiber with the binder is preferably stirring, and the stirring time is preferably 0.5 to 2 hours, more preferably 1 to 2 hours. The present invention can fully mix the powder materials with the binder by stirring.

[0047] The preparation method provided by the present invention is simple to operate, and a dispersed and stable low-temperature curing phosphate coating can be obtained by mixing and reacting various materials.

[0048] The present invention also provides a method for using the low-temperature curing phosphate coating described in the above technical solution, comprising: coating the low-temperature curing phosphate coating on a substrate, and sequentially performing low-temperature heat treatment and high-temperature heat treatment to obtain a coating.

[0049] In the present invention, the substrate preferably includes carbon steel, stainless steel, titanium, aluminum, aluminum alloy or magnesium alloy. In the present invention, since the coating has a strong bonding force, it can be applied to a variety of substrates.

[0050] The present invention has no particular limitation on the coating method, and any conventional coating method can be used. In the present invention, the coating method preferably includes dipping, brushing or spraying. The present invention has no particular limitation on the parameters of the dipping, brushing or spraying, and the parameters can be adjusted as needed to form a coating layer with uniform thickness on the substrate.

[0051] In the present invention, the coating layer formed by coating preferably has a thickness of 5 to 80 μm, more preferably 10 to 70 μm. The present invention controls the thickness of the coating layer within the above range, and after the coating layer is cured, a coating with uniform thickness and strong bonding ability with the substrate can be obtained.

[0052] In the present invention, the temperature of the low-temperature heat treatment is 60-80°C, preferably 65-70°C; the holding time of the low-temperature heat treatment is preferably 30-120min, more preferably 60-120min; the temperature of the high-temperature heat treatment is preferably 150-200°C, more preferably 160-180°C; the holding time of the high-temperature heat treatment is preferably 30-120min, more preferably 60-120min. The present invention first helps to improve the density of the coating and reduce the microporous structure of the coating, increase the film density of the coating, and promote the curing of the coating through high-temperature heat treatment to form a dense coating.

[0053] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0054] Example 1 Raw materials: phosphoric acid with a mass concentration of 85%; polyvinyl alcohol is polyvinyl alcohol 1788; fused quartz: particle size is 5~8μm; nano-silicon dioxide: particle size is 5~10nm; fiber: glass fiber with a length of 60~80μm and a diameter of 10~20μm; A low-temperature curing phosphate coating is prepared from the following raw materials, calculated by mass content: 45% aluminum powder, 6% phosphoric acid, 3% aluminum hydroxide, 3% chromic anhydride, 5% zirconium sol, 2% polyvinyl alcohol-coated magnesium oxide, 1% cerium oxide, 1.5% ethanolamine, 1% fused quartz, 1% nano-silicon dioxide, 1% fiber and the balance water; The preparation method of polyvinyl alcohol-coated magnesium oxide is as follows: 5 g of magnesium oxide, 1.5 g of polyvinyl alcohol 1788 and 300 mL of water are ultrasonically treated for 1 hour, then filtered, and the filter residue is washed with deionized water, and then dried at 40° C. for 24 hours to obtain polyvinyl alcohol-coated magnesium oxide; The preparation method of the above-mentioned low-temperature curing phosphate coating comprises the following steps: (1) Phosphoric acid, chromic anhydride and water were stirred at 85°C for 0.5 h to be uniformly mixed, and then aluminum hydroxide was added to the obtained mixed system, and the stirring was continued for 0.5 h to obtain a mixed slurry; (2) mixing polyvinyl alcohol-coated magnesium oxide, rare earth oxide and organic alcohol amine with the slurry obtained in step (1) at 90° C. for 1 hour to obtain a binder; (3) Aluminum powder, zirconium sol, fused quartz, nano-silica and fiber are stirred with the binder obtained in step (2) for 2 hours to obtain a low-temperature curing phosphate coating.

[0055] Example 2 The difference from Example 1 is that the low-temperature curing phosphate coating is prepared from the following raw materials, calculated by mass content: 45% aluminum powder, 6% phosphoric acid, 3% aluminum hydroxide, 3% chromic anhydride, 5% zirconium sol, 2% polyvinyl alcohol-coated magnesium oxide, 1.5% cerium oxide, 2% ethanolamine, 2% fused quartz, 2% nano-silicon dioxide, 2% fiber and the balance water; The remaining parameters are the same as those in Example 1.

[0056] Example 3 The difference from Example 1 is that the low-temperature curing phosphate coating is prepared from the following raw materials by mass content: 45% aluminum powder, 6% phosphoric acid, 3% aluminum hydroxide, 3% chromic anhydride, 5% zirconium sol, 2% polyvinyl alcohol-coated magnesium oxide, 1.5% cerium oxide, 3% diethanolamine, 2% fused quartz, 2% nano-silicon dioxide, 2% fiber and the balance water; The remaining parameters are the same as those in Example 1.

[0057] Example 4 The difference from Example 1 is that the low-temperature curing phosphate coating is prepared from the following raw materials by mass content: 45% aluminum powder, 6% phosphoric acid, 3% aluminum hydroxide, 3% chromic anhydride, 5% zirconium sol, 2% polyvinyl alcohol-coated magnesium oxide, 1.5% lanthanum oxide, 2% diethanolamine, 3% fused quartz, 3% nano-silicon dioxide, 3% fiber and the balance water; The remaining parameters are the same as those in Example 1.

[0058] Example 5 The difference from Example 1 is that the low-temperature curing phosphate coating is prepared from the following raw materials by mass content: 45% aluminum powder, 6% phosphoric acid, 3% aluminum hydroxide, 3% chromic anhydride, 5% zirconium sol, 2% polyvinyl alcohol-coated magnesium oxide, 1.5% lanthanum oxide, 2% diethanolamine, 3% fused quartz, 4% nano-silicon dioxide, 4% fiber and the balance water; The remaining parameters are the same as those in Example 1.

[0059] Comparative Example 1 The difference from Example 1 is that the phosphate coating is prepared from the following raw materials, calculated by mass content: 45% aluminum powder, 6% phosphoric acid, 3% aluminum hydroxide, 3% chromic anhydride, 5% zirconium sol, 2% polyvinyl alcohol-coated magnesium oxide, 1% cerium oxide, 1.5% ethanolamine, 1% nano-silicon dioxide and the balance water; The remaining parameters are the same as those in Example 1.

[0060] Comparative Example 2 The difference from Example 1 is that the phosphate coating is prepared from the following raw materials, calculated by mass content: 45% aluminum powder, 6% phosphoric acid, 3% aluminum hydroxide, 3% chromic anhydride, 5% zirconium sol, 2% magnesium oxide, 1% fused quartz, 1% nano-silicon dioxide, 1% fiber and the balance water; The remaining parameters are the same as those in Example 1.

[0061] Comparative Example 3 The difference from Example 1 is that the phosphate coating is prepared from the following raw materials, calculated by mass content: 45% aluminum powder, 6% phosphoric acid, 3% aluminum hydroxide, 3% chromic anhydride, 5% zirconium sol, 2% magnesium oxide and the balance water; The remaining parameters are the same as those in Example 1.

[0062] Comparative Example 4 A traditional phosphate coating is prepared from the following raw materials, calculated by weight: 45% aluminum powder, 10% phosphoric acid, 3% aluminum hydroxide, 3% chromic anhydride, 5% magnesium oxide and the balance water.

[0063] Test Case The phosphate coatings prepared in Examples 1 to 5 and Comparative Examples 1 to 3 were respectively sprayed onto a stainless steel substrate with an average thickness of 60 μm, and then subjected to low-temperature heat treatment by keeping the temperature at 60° C. for 30 min, and then subjected to high-temperature heat treatment by keeping the temperature at 160° C. for 60 min, and then cooled to room temperature with the furnace to obtain a low-temperature cured phosphate coating.

[0064] The traditional phosphate coating prepared in Comparative Example 4 was sprayed onto the stainless steel substrate with an average thickness of 60 μm, and then low-temperature heat treatment was performed by keeping the temperature at 80° C. for 30 min, and then high-temperature heat treatment was performed by keeping the temperature at 300° C. for 60 min, and the coating was cooled to room temperature with the furnace to obtain a low-temperature cured phosphate coating.

[0065] The coatings prepared in the examples and comparative examples were tested for performance, and the results are shown in Table 1 below: Table 1 Test results of coating properties obtained by curing the coatings prepared in the examples and comparative examples

[0066] In Table 1, the test method for high and low temperature thermal shock resistance is: the coated stainless steel substrate is kept at 550°C for 30 minutes, cooled in cold water, and then kept at 550°C for 30 minutes, and the test is repeated 100 times. Observe whether the coating has fallen off or cracked.

[0067] It can be seen from Table 1 that the adhesion and neutral salt spray resistance of Comparative Example 1 are lower than those of Example 1. This is because the difference between Comparative Example 1 and Example 1 is that fused quartz and fiber are not added, and fused quartz is used as aggregate to make the coating have higher mechanical strength and is conducive to improving the adhesion of the coating; fiber is used as filler, and when the coating is cured, the binder will spread along the fiber to improve the density of the coating; therefore, the adhesion and neutral salt spray resistance of Comparative Example 1 are lower than those of Example 1.

[0068] Compared with Example 1, Comparative Example 2 uses magnesium oxide instead of polyvinyl alcohol to coat magnesium oxide, cerium oxide and ethanolamine, and cerium oxide and ethanolamine are key factors in reducing the curing temperature. The effect of using magnesium oxide alone to reduce the curing temperature is limited. Therefore, the prepared coating is kept at 60°C for 30 minutes for low-temperature heat treatment, and then kept at 160°C for 60 minutes for high-temperature heat treatment. The curing effect is poor, and moisture resorption occurs. In addition, the various performances of Comparative Example 2 are worse than those of Example 1.

[0069] Compared with Example 1, Comparative Example 3 uses magnesium oxide to replace polyvinyl alcohol to coat magnesium oxide, and does not add cerium oxide, ethanolamine, fused quartz, nano-silica and fiber. Since cerium oxide and ethanolamine are key factors in reducing the curing temperature, the effect of using magnesium oxide alone to reduce the curing temperature is limited, and fused quartz is used as an aggregate to give the coating a higher mechanical strength and is conducive to improving the adhesion of the coating; the fiber is used as a filler, and when the coating is cured, the binder will spread along the fiber to improve the density of the coating. Therefore, the various properties of Comparative Example 3 are worse than those of Example 1.

[0070] Comparative Example 4 is a common traditional phosphate coating, which can be cured at high temperature and has good performance, but cannot achieve low temperature curing. According to the comparison between Comparative Example 4 and Example 1, it can be seen that the method provided by the present invention can not only achieve low temperature curing by improving the components, but also the performance of the cured coating reaches the technical effect equivalent to that of the traditional high temperature curing phosphate coating, solving the problem of poor comprehensive mechanical properties of low temperature curing phosphate coating.

[0071] It can be seen from the results of the above examples that the phosphate coating provided by the present invention has a lower curing temperature. Moreover, the coating obtained under the premise of achieving low-temperature curing has comprehensive mechanical properties comparable to those of conventional high-temperature cured phosphate coatings, solving the problem of decreased comprehensive mechanical properties of conventional low-temperature cured phosphate coatings after low-temperature curing.

[0072] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A low-temperature curing phosphate coating is prepared from raw materials including the following components by mass content: 40-70% aluminum powder, 6-15% phosphoric acid, 2-5% aluminum hydroxide, 1-3% chromic anhydride, 5-10% zirconium sol, 1-2% polyvinyl alcohol-coated magnesium oxide, 0.5-2% rare earth oxide, 1.5-3% organic alcohol amine, 0.5-3% fused quartz, 0.5-5% nano-silicon dioxide, 0.5-5% fiber and the balance water.

2. The low temperature curing phosphate coating according to claim 1, characterized in that: The preparation method of the polyvinyl alcohol-coated magnesium oxide comprises: mixing magnesium oxide, polyvinyl alcohol and water to obtain the polyvinyl alcohol-coated magnesium oxide.

3. The low temperature curing phosphate coating according to claim 1, characterized in that: The rare earth oxides include cerium oxide and / or lanthanum oxide.

4. The low temperature curing phosphate coating according to claim 1, characterized in that: The organic alcoholamine includes ethanolamine, diethanolamine or isopropanolamine.

5. The low temperature curing phosphate coating according to claim 1, characterized in that: The particle size of the fused quartz is 5-10 μm.

6. The low temperature curing phosphate coating according to claim 1, characterized in that: The particle size of the nano silicon dioxide is 5-20 nm.

7. The low temperature curing phosphate coating according to claim 1, characterized in that: The diameter of the fiber is 5-20 μm; the length of the fiber is 50-100 μm.

8. The low temperature curing phosphate coating according to claim 1 or 7, characterized in that: The fibers include glass fibers and / or silica fibers.

9. The method for preparing the low temperature curing phosphate coating according to any one of claims 1 to 8, comprising the following steps: (1) mixing phosphoric acid, aluminum hydroxide, chromic anhydride and water to obtain a mixed slurry; (2) mixing polyvinyl alcohol-coated magnesium oxide, rare earth oxide and organic alcohol amine with the slurry obtained in step (1) to obtain a binder; (3) Aluminum powder, zirconium sol, fused quartz, nano-silicon dioxide and fiber are mixed with the binder obtained in step (2) to obtain a low-temperature curing phosphate coating.

10. A method for using the low-temperature curing phosphate coating according to any one of claims 1 to 8 or the low-temperature curing phosphate coating prepared by the preparation method according to claim 9, comprising: Applying a low-temperature curing phosphate coating to a substrate, and sequentially performing a low-temperature heat treatment and a high-temperature heat treatment to obtain a coating; The temperature of the low-temperature heat treatment is 60-80°C, and the insulation time of the low-temperature heat treatment is 30-120 minutes; the temperature of the high-temperature heat treatment is 150-200°C, and the insulation time of the high-temperature heat treatment is 30-120 minutes.

Citation Information

Patent Citations

  • Low-temperature curing wear-resistant inorganic phosphate bonded solid lubricating coating material and preparation method thereof

    CN114196239A

  • Low-temperature curing phosphate protective coating and preparation and curing method thereof

    CN115011150A

  • Low-temperature curing phosphate coating and preparation method thereof

    CN115612318A

  • Alcohol amine low-temperature curing high-temperature-corrosion-resistant protective coating

    CN118271878A